Sustainable Resource Based Materials in Food Packaging Design - Nur Hidayah Azhar; Nor Zalifah Zainal Abidin (Cultural Syndrome, 2020)
This paper provides and understanding on the utilization of sustainable resources in food packaging. It reviews the negative impacts of plastic and current sustainable materials that are used to substitute plastic in food packaging. In order to replace plastics, many researches have been done to surmount the issue and biodegradable materials such as cellulose, plant fibres, starch based, and any bio-based material have undergone research and experiments to achieve the plastic free food packaging. Moreover, there has been strength and weaknesses in every bio-based material that need to be considered such as its polymer structure and its ability to withstand the outside properties. Different composition and structure of the polymer from this bio-based material determine the shelf life of a food when they are used as the packaging and how it can affect the food. Lesser additives of chemicals used to support the polymer is better. However, much research is still needed in discovering which bio-based material is the most suitable to use as the permanent eco-friendly food packaging design.